An Unexplored 11th Century Gospel Lectionary in Sydney - Gerber, Albrecht (Buried History: The Journal of the Australian Institute of Archaeology, 2018)
This paper draws attention to an unexplored document of historical significance, namely the Codex Angus. It is a 1000-year-old Greek parchment lectionary held by the archive of the Sydney University’s Rare Book and Special Collections Library. The codex was brought from Germany to Australia in 1936 and although at that time it was lauded in The Sydney Morning Herald as ‘of marvellous beauty of workmanship, and in perfect condition,’ it remains almost completely unknown and has never yet been seriously analysed. This paper investigates the checkered history of the manuscript’s journey to Sydney and signals its potential usefulness to codicology, textual criticism, palaeography, or even social anthropology.